Effects of Plotytarya strohilacea Sieb. et Zuce Tannin on the Growth Performance, Oxidation Resistance, Intestinal Morphology and Cecal Microbial Composition of Broilers - Tong, Zhenkai; Lei, Fuhong; Liu, Lixuan; Wang, Fei; Guo, Aiwei (Frontiers in Veterinary Science, 2022)
A total of 360 one-day-old Arbor Acres male broiler chicks were randomly divided into 4 dietary treatment groups, with 6 replicates per group and 15 broilers per replicate. The control group (Control) was fed the basic diet, and the experimental groups PT1 and PT2 and PT3 were fed the basic diet supplemented with 100, 400, and 800 mg/kg Plotytarya strohilacea Sieb. et Zuce tannins for 42 days. The results showed that the average daily feed intake (ADFI) of the PT1 group was significantly lower than that of the Control group, and there was a significant quadratic relationship between the ADFI and the concentration of Plotytarya strohilacea Sieb. et Zuce tannin (P<0.05). Compared with the PT0 group, the F/G of 22- to 42-day-old broilers in the PT1 group showed a decreasing trend (P=0.068). The serum catalase (CAT) activity in the PT1 group was significantly higher than those of the other three groups, and the effect was significantly quadratically related to the dosage (P<0.05). The glutathione peroxidase (GSH-Px) levels in the PT1, PT2 and Control groups were significantly higher than that of the PT3 group, and the effect was significantly quadratically related to the addition amount (P<0.05). The serum total antioxidant capacity (T-AOC) in the PT1 group was significantly higher than that in the Control group, and the effect was significantly quadratically related to the addition amount (P<0.05). Compared to the Control group, the heights of jejunum villi in the PT1, PT2 and PT3 groups were significantly higher, and there was a significant quadratic relationship between the height of jejunum villi and the addition amount (P<0.05). In addition, adding Plotytarya strohilacea Sieb. et Zuce tannins to diets significantly increased Parabacteroides in the dominant genus (P<0.05). In conclusion, dietary supplementation with Plotytarya strohilacea Sieb. et Zuce tannin improved the growth performance, antioxidant function, and intestinal morphology along with an increased abundance of Parabacteroides in the cecum, and the recommended dosage of Plotytarya strohilacea Sieb. et Zuce tannin in broiler diets was 100 mg/kg.